Regulation and control method for in-situ authigenic nano precipitated phase in selective laser melting process of high-strength heat-resistant aluminum alloy
Through thermodynamic analysis and first-principle calculation, select appropriate trace elements, combine laser selection melting and multi-step solid solution-aging process, multi-layer composite high-thermal stability nanoprecipitation phases, solving the nanoprecipitation phase stability problem of Al-Cu-based alloys under high-temperature service conditions, and achieving the improvement of the heat resistance of the material.
Patent Information
- Application Number
- CN202411814716.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-11
AI Technical Summary
Under additive manufacturing technology, the Ostwald maturation problem of the nano-precipitation phase of Al-Cu alloy under high-temperature service conditions has led to insufficient heat resistance.
Through thermodynamic analysis and first-principle calculation, appropriate trace elements are selected to form high-temperature and stable Al-Cu-X alloy; during the laser selection melting process, process parameters are regulated to avoid microsegregation of solute atoms; multi-layer composite high-thermal stability nanoprecipitation phase is designed using a multi-step solid solution-aging process.
The heat resistance performance of Al-Cu-X alloy in the range of 300℃-400℃ was greatly improved, and the stability problem of nano-precipitation phase at high temperatures was solved.
Smart Images

Figure CN119794373A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for regulating in-situ self-generated nano-precipitated phases during laser selective melting of a high-strength heat-resistant aluminum alloy, and belongs to the field of material science and engineering. Background Art
[0002] With the increasingly urgent demand for lightweight materials in the fields of aerospace, transportation, weapons and equipment, new high-strength aluminum alloys have gradually become an indispensable key research and development target in the industry. At the same time, as the service temperature of many components gradually crosses from room temperature to the range of 300℃-400℃, higher requirements are placed on the heat resistance of materials. Considering that the heat resistance of alloys is positively correlated with their melting point and specific gravity, that is, the higher the melting point and the greater the specific gravity, the higher the heat resistance temperature, and vice versa, the research and development of lightweight, low-melting-point heat-resistant alloys has become one of the focuses of international competition in the field of metal materials. Compared with other metal materials, Al-Cu alloys have the characteristics of both lightweight and high strength, making them the most competitive light alloy heat-resistant materials.
[0003] Al-Cu alloys are age-hardened aluminum alloys, and are also currently recognized by the industry as the most suitable aluminum alloy system for high-temperature service. There are two reasons for this: First, the diffusion rate of Cu in the α-Al matrix is lower than that of alloying elements such as Mg, Zn, and Si, and the intrinsic thermal stability of the precipitated phase is relatively high, so it has better high-temperature performance than other lightweight aluminum alloys. Second, the precipitation sequence of the Cu-related precipitation phase is clear, and the θ'-Al2Cu and Ω phases have coherent / semi-coherent interfaces. The precipitation strategy can be theoretically designed to control the main composition of the precipitation phase and achieve high-concentration interfacial solute segregation.
[0004] However, additive manufacturing technology has put forward new requirements for high-strength Al-Cu alloys. This is because compared with traditional casting methods, additive manufacturing such as selective laser melting (SLM) and electron beam melting (EBM) usually has a very high cooling rate (up to 10 4 Up to 10 6 ℃ / s). This rapid cooling will lead to fine grain size and unbalanced microstructure. This also means that the aging strengthening mechanism of Al-Cu alloy in traditional casting environment cannot meet the needs of additive manufacturing, and the stability of the precipitation strengthening phase of Al-Cu alloy is destroyed. This is restricting the further application of additive manufacturing high-strength aluminum alloy under high-temperature service conditions. Summary of the invention
[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a method for regulating in-situ self-generated nano-precipitation phase during laser selective melting of high-strength and heat-resistant aluminum alloy, so as to solve the problems raised in the above background technology.
[0006] In order to achieve the above object, the present invention is implemented by the following technical scheme: a method for regulating in-situ self-generated nano-precipitation phase during laser selective melting of high-strength heat-resistant aluminum alloy, comprising the following steps:
[0007] Step 1: Precipitation phase selection based on thermodynamic analysis and first-principles calculations;
[0008] ①. The high temperature precipitation phase composition of Al-Cu-X alloy is obtained by adding trace elements;
[0009] ②. Clarify the thermodynamic stability of different precipitated phases at high temperatures through first-principles calculations;
[0010] ③. Obtain the composite precipitate phase with the best resistance to high temperature coarsening through thermodynamic equilibrium analysis;
[0011] Step 2: Non-equilibrium microstructure control of high-strength and heat-resistant aluminum alloy under laser selective melting;
[0012] ①. Simulate the heat / flow field under different process parameters through numerical simulation;
[0013] ② Avoid micro-segregation of solute atoms by adjusting parameters such as scanning speed and laser power;
[0014] ③. Non-equilibrium organization regulation by achieving optimal process parameters;
[0015] Step 3: Study on the in-situ nanophase precipitation strategy under multi-step solution-aging process;
[0016] ①. Study the influence of solid solution parameters on the microstructure of Al-Cu-X alloy under magnetic field;
[0017] ② Design a multi-step regression and re-aging process to obtain a multi-layer composite nano-precipitate phase with high thermal stability;
[0018] ③. Conduct high temperature performance evaluation of Al-Cu-X alloy to verify the in-situ autogenous precipitation phase screening criteria.
[0019] Specifically, in step 1, based on Thermo-Calc thermodynamic software and its aluminum-based database TCAL, binary and ternary phase diagrams when different rare earth elements (RE) such as Ce, Er, etc. and different transition elements (TM) such as Sc, Mn, Zr, etc. are added to the Al-Cu binary alloy are calculated to obtain a series of Al-Cu-X alloy phase compositions at different temperatures;
[0020] Based on Material Studio, the thermal stability of different precipitates was analyzed. Through comparative analysis of binding energy, formation energy, phonon spectrum, and Gibbs free energy, the thermal decomposition tendency of different precipitates at 300°C, 350°C, and 400°C was obtained, the stability time of different types of precipitates under high-temperature service conditions was clarified, and the transformation rules of different precipitates in Al-Cu-X alloy at 300°C, 350°C, and 400°C were predicted.
[0021] Through one-to-one or one-to-many combinations of rare earth elements and transition elements, thermodynamic equilibrium analysis and multivariate phase diagram calculation of different precipitate phases are carried out to clarify the phase composition of aluminum alloys under different temperature conditions such as 300°C, 350°C, and 400°C, and obtain the composite precipitate phase with the best resistance to high-temperature coarsening.
[0022] Specifically, in step 2, the thermophysical properties of the material, such as specific heat, thermal conductivity, melting point and density, which are key factors affecting the heat / flow field, are input; the formation, development and solidification process of the molten pool, as well as the resulting fluid dynamics effects, are simulated; the temperature distribution throughout the manufacturing process is predicted, including the heat-affected zone of the molten pool area and the surrounding material;
[0023] By reducing the laser power, the size and depth of the molten pool can be reduced, thereby reducing the thermal gradient inside the molten pool and reducing the diffusion and segregation of solute elements due to heat-driven; By reducing the laser power, the size and depth of the molten pool can be reduced, thereby reducing the thermal gradient inside the molten pool and reducing the diffusion and segregation of solute elements due to heat-driven;
[0024] Through experimental design methods (such as orthogonal experiments, response surface methodology, etc.), the key process parameters that affect the formation of non-equilibrium structure are determined, and the optimal parameter combination is found. The experimental results are combined with simulation predictions to verify and optimize the process parameters and achieve more precise non-equilibrium structure regulation.
[0025] Specifically, in step 3, the influence of factors such as solution temperature, solution time, and quenching medium on the Al-Cu-X alloy obtained by additive manufacturing is studied; while eliminating the low-melting point non-equilibrium phase that may exist in the alloy, the solution process parameters that can completely dissolve the grain boundary θ-Al2Cu phase are obtained, and the fine grain structure under the action of the magnetic field is retained in the solution structure as much as possible;
[0026] According to the results of thermodynamic equilibrium analysis of different nano-precipitated phases, a multi-step regression re-aging heat treatment process is designed, such as 250℃ / 8h+450℃ / 20min+250℃ / 6h. The core of the process is to avoid the difference in precipitation temperature between different precipitated phases, such as θ′-Al2Cu and Al3X, so that two or more phases are precipitated alternately, and the nano-precipitated phase presents a multi-layer composite structure, thereby avoiding the occurrence of thermal coarsening of the nano-precipitated phase.
[0027] The high-temperature performance of the Al-Cu-X alloy after multi-step solution-aging was tested, and its high-temperature tensile strength was analyzed. The microalloying design and precipitation phase screening criteria of the Al-Cu alloy were verified, and the in-situ self-generated nanophase precipitation strategy of the Al-Cu-X alloy was obtained, achieving a significant improvement in the heat resistance of aluminum alloy materials in the range of 300℃-400℃.
[0028] Beneficial effects of the present invention:
[0029] Through the design and regulation of high thermal stability nano-precipitates under additive manufacturing, the interfacial energy between the precipitates and the α-Al matrix under rapid cooling conditions is reduced, and the segregated atoms are forced to pin the interface, which can achieve the stabilization of the precipitates caused by the segregation of solute atoms at the heterogeneous interface, and reverse the Ostwald ripening problem of nano-precipitates in Al-Cu alloys at service temperatures above 200°C. It has important scientific significance and practical value in promoting the additive manufacturing of high-strength and heat-resistant aluminum alloys. Combining high-strength and heat-resistant aluminum alloys with additive manufacturing technology can achieve rapid design and coupled iteration of material composition and process measures.
[0030] The design principles and control strategies of in-situ self-generated nano-precipitates with high thermal stability are clarified. The physical and chemical nature of the formation of precipitates is clarified, the thermodynamic stability process of different types of precipitates is clarified, and the composite precipitates with the best resistance to high-temperature coarsening are obtained. While introducing additive manufacturing to control the microstructure and grain size of the cast alloy, a multi-step solution-aging process is used to prepare a nano-precipitate phase with a multi-layer composite structure, so as to achieve a significant improvement in the heat resistance of Al-Cu-X (X=RE, TM) alloy materials in the high-temperature service range of 300℃-400℃. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0032] Figure 1 It is a technical roadmap of the method for controlling the in-situ self-generated nano-precipitated phase during the laser selective melting process of the high-strength and heat-resistant aluminum alloy of the present invention;
[0033] Figure 2 Schematic diagram of multi-step regression re-aging: (a) aging path; (b) types and size distribution of precipitated phases at different stages; DETAILED DESCRIPTION
[0034] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.
[0035] See also Figure 1 to Figure 2The present invention provides a technical solution: a method for regulating in-situ self-generated nano-precipitation phase during laser selective melting of high-strength and heat-resistant aluminum alloy, comprising the following steps:
[0036] Step 1: Precipitation phase selection based on thermodynamic analysis and first-principles calculations;
[0037] ①. The high temperature precipitation phase composition of Al-Cu-X alloy is obtained by adding trace elements;
[0038] ②. Clarify the thermodynamic stability of different precipitated phases at high temperatures through first-principles calculations;
[0039] ③. Obtain the composite precipitate phase with the best resistance to high temperature coarsening through thermodynamic equilibrium analysis;
[0040] Step 2: Non-equilibrium microstructure control of high-strength and heat-resistant aluminum alloy under laser selective melting;
[0041] ①. Simulate the heat / flow field under different process parameters through numerical simulation;
[0042] ② Avoid micro-segregation of solute atoms by adjusting parameters such as scanning speed and laser power;
[0043] ③. Non-equilibrium organization regulation by achieving optimal process parameters;
[0044] Step 3: Study on the in-situ nanophase precipitation strategy under multi-step solution-aging process;
[0045] ①. Study the influence of solid solution parameters on the microstructure of Al-Cu-X alloy under magnetic field;
[0046] ② Design a multi-step regression and re-aging process to obtain a multi-layer composite nano-precipitate phase with high thermal stability;
[0047] ③. Conduct high temperature performance evaluation of Al-Cu-X alloy to verify the in-situ autogenous precipitation phase screening criteria.
[0048] Specifically, in step 1, based on Thermo-Calc thermodynamic software and its aluminum-based database TCAL, binary and ternary phase diagrams when different rare earth elements (RE) such as Ce, Er, etc. and different transition elements (TM) such as Sc, Mn, Zr, etc. are added to the Al-Cu binary alloy are calculated to obtain a series of Al-Cu-X alloy phase compositions at different temperatures;
[0049] Based on Material Studio, the thermal stability of different precipitates was analyzed. Through comparative analysis of binding energy, formation energy, phonon spectrum, and Gibbs free energy, the thermal decomposition tendency of different precipitates at 300°C, 350°C, and 400°C was obtained, the stability time of different types of precipitates under high-temperature service conditions was clarified, and the transformation rules of different precipitates in Al-Cu-X alloy at 300°C, 350°C, and 400°C were predicted.
[0050] Through one-to-one or one-to-many combinations of rare earth elements and transition elements, thermodynamic equilibrium analysis and multivariate phase diagram calculation of different precipitate phases are carried out to clarify the phase composition of aluminum alloys under different temperature conditions such as 300°C, 350°C, and 400°C, and obtain the composite precipitate phase with the best resistance to high-temperature coarsening.
[0051] Specifically, in step 2, the thermophysical properties of the material, such as specific heat, thermal conductivity, melting point and density, which are key factors affecting the heat / flow field, are input; the formation, development and solidification process of the molten pool, as well as the resulting fluid dynamics effects, are simulated; the temperature distribution throughout the manufacturing process is predicted, including the heat-affected zone of the molten pool area and the surrounding material;
[0052] By reducing the laser power, the size and depth of the molten pool can be reduced, thereby reducing the thermal gradient inside the molten pool and reducing the diffusion and segregation of solute elements due to heat-driven; By reducing the laser power, the size and depth of the molten pool can be reduced, thereby reducing the thermal gradient inside the molten pool and reducing the diffusion and segregation of solute elements due to heat-driven;
[0053] Through experimental design methods (such as orthogonal experiments, response surface methodology, etc.), the key process parameters that affect the formation of non-equilibrium structure are determined, and the optimal parameter combination is found. The experimental results are combined with simulation predictions to verify and optimize the process parameters and achieve more precise non-equilibrium structure regulation.
[0054] Specifically, in step 3, the influence of factors such as solution temperature, solution time, and quenching medium on the Al-Cu-X alloy obtained by additive manufacturing is studied; while eliminating the low-melting point non-equilibrium phase that may exist in the alloy, the solution process parameters that can completely dissolve the grain boundary θ-Al2Cu phase are obtained, and the fine grain structure under the action of the magnetic field is retained in the solution structure as much as possible;
[0055] According to the results of thermodynamic equilibrium analysis of different nano-precipitated phases, a multi-step regression re-aging heat treatment process is designed, such as 250℃ / 8h+450℃ / 20min+250℃ / 6h. The core of the process is to avoid the difference in precipitation temperature between different precipitated phases, such as θ′-Al2Cu and Al3X, so that two or more phases are precipitated alternately, and the nano-precipitated phase presents a multi-layer composite structure, thereby avoiding the occurrence of thermal coarsening of the nano-precipitated phase.
[0056] The high-temperature performance of the Al-Cu-X alloy after multi-step solution-aging was tested, and its high-temperature tensile strength was analyzed. The microalloying design and precipitation phase screening criteria of the Al-Cu alloy were verified, and the in-situ self-generated nanophase precipitation strategy of the Al-Cu-X alloy was obtained, achieving a significant improvement in the heat resistance of aluminum alloy materials in the range of 300℃-400℃.
[0057] The nano-precipitation strengthening phase in Al-Cu alloy is mainly θ′-Al2Cu, but this phase is very easy to coarsen (ripen) at a temperature greater than 200℃, thereby losing its precipitation strengthening effect. In order to achieve long-term use of Al-Cu alloy under high temperature (300℃-400℃) service conditions, it is necessary to find new strengthening phases to compensate for the high-temperature failure of the θ′ phase. Therefore, by combining thermodynamic analysis and first-principles calculations, the precipitation sequence and high-temperature thermodynamic stability of different rare earth elements RE (such as Ce, Er) or different transition elements TM (such as Sc, Mn, Zr) are studied, and the correlation between the heat-resistant precipitation phase and the θ′ phase is analyzed, thereby realizing the design and optimization of in-situ self-generated nano-precipitation phase with high thermal stability in Al-Cu alloy.
[0058] The heat treatment parent material of Al-Cu-X alloy has a great influence on the heat treatment organization. This is because the uneven distribution of components or the large size of some precipitated phases will cause the rare earth or transition elements to be unable to be completely dissolved into the matrix in the subsequent solid solution treatment. Therefore, the solidification process of Al-Cu-X alloy is adjusted by additive manufacturing technology in order to obtain a good parent material. Subsequently, a graded multi-step aging process is used to adjust the precipitation order of different nano-precipitated phases to form a multi-layer shell-like composite nano-precipitated phase. Through the solid solution aging heat treatment under the coordination of the external field, the high stability of the nano-precipitated phase under high temperature conditions is achieved. This ensures that the Al-Cu-X alloy reaches the heat resistance target.
[0059] Through the design and regulation of high thermal stability nano-precipitates under additive manufacturing, the interfacial energy between the precipitates and the α-Al matrix under rapid cooling conditions is reduced, and the segregated atoms are forced to pin the interface, which can achieve the stabilization of the precipitates caused by the segregation of solute atoms at the heterogeneous interface, and reverse the Ostwald ripening problem of nano-precipitates in Al-Cu alloys at service temperatures above 200°C. It has important scientific significance and practical value in promoting the additive manufacturing of high-strength and heat-resistant aluminum alloys. Combining high-strength and heat-resistant aluminum alloys with additive manufacturing technology can achieve rapid design and coupled iteration of material composition and process measures.
[0060] The design principles and control strategies of in-situ self-generated nano-precipitates with high thermal stability are clarified. The physical and chemical nature of the formation of precipitates is clarified, the thermodynamic stability process of different types of precipitates is clarified, and the composite precipitates with the best resistance to high-temperature coarsening are obtained. While introducing additive manufacturing to control the microstructure and grain size of the cast alloy, a multi-step solution-aging process is used to prepare a nano-precipitate phase with a multi-layer composite structure, so as to achieve a significant improvement in the heat resistance of Al-Cu-X (X=RE, TM) alloy materials in the high-temperature service range of 300℃-400℃.
[0061] Although this specification is described according to implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for regulating in-situ self-generated nano-precipitation phase during laser selective melting of high-strength and heat-resistant aluminum alloy, characterized in that The steps include: Step 1: Precipitation phase selection based on thermodynamic analysis and first-principles calculations; ①. The high temperature precipitation phase composition of Al-Cu-X alloy is obtained by adding trace elements; ②. Clarify the thermodynamic stability of different precipitated phases at high temperatures through first-principles calculations; ③. Obtain the composite precipitate phase with the best resistance to high temperature coarsening through thermodynamic equilibrium analysis; Step 2: Non-equilibrium microstructure control of high-strength and heat-resistant aluminum alloy under laser selective melting; ①. Simulate the heat / flow field under different process parameters through numerical simulation; ② Avoid micro-segregation of solute atoms by adjusting parameters such as scanning speed and laser power; ③. Non-equilibrium organization regulation by achieving optimal process parameters; Step 3: Study on the in-situ nanophase precipitation strategy under multi-step solution-aging process; ①. Study the influence of solid solution parameters on the microstructure of Al-Cu-X alloy under magnetic field; ② Design a multi-step regression and re-aging process to obtain a multi-layer composite nano-precipitate phase with high thermal stability; ③. Conduct high temperature performance evaluation of Al-Cu-X alloy to verify the in-situ autogenous precipitation phase screening criteria.
2. The method for controlling in-situ self-generated nano-precipitated phase during laser selective melting of high-strength and heat-resistant aluminum alloy according to claim 1, characterized in that: In the step 1, based on the Thermo-Calc thermodynamic software and its aluminum-based database TCAL, the binary and ternary phase diagrams of different rare earth elements and different transition elements added to the Al-Cu binary alloy are calculated to obtain a series of phase compositions of Al-Cu-X alloys at different temperatures; Based on Material Studio, the thermal stability of different precipitates was analyzed. Through comparative analysis of binding energy, formation energy, phonon spectrum, and Gibbs free energy, the thermal decomposition tendency of different precipitates at 300°C, 350°C, and 400°C was obtained, the stability time of different types of precipitates under high-temperature service conditions was clarified, and the transformation rules of different precipitates in Al-Cu-X alloy at 300°C, 350°C, and 400°C were predicted. Through one-to-one or one-to-many combinations of rare earth elements and transition elements, thermodynamic equilibrium analysis and multivariate phase diagram calculation of different precipitate phases are carried out to clarify the phase composition of aluminum alloys under different temperature conditions of 300°C, 350°C, and 400°C, and obtain the composite precipitate phase with the best resistance to high-temperature coarsening.
3. The method for controlling in-situ self-generated nano-precipitated phase during laser selective melting of high-strength and heat-resistant aluminum alloy according to claim 1, characterized in that: In step 2, the thermophysical properties of the material are input: specific heat, thermal conductivity, melting point and density, which are key factors affecting the heat / flow field; the formation, development and solidification process of the molten pool and the resulting fluid dynamic effects are simulated; the temperature distribution throughout the manufacturing process is predicted, including the heat-affected zone of the molten pool area and the surrounding material; By reducing the laser power, the size and depth of the molten pool can be reduced, thereby reducing the thermal gradient inside the molten pool and reducing the diffusion and segregation of solute elements due to heat-driven; By reducing the laser power, the size and depth of the molten pool can be reduced, thereby reducing the thermal gradient inside the molten pool and reducing the diffusion and segregation of solute elements due to heat-driven; The key process parameters that affect the formation of non-equilibrium tissue are determined through experimental design methods, and the optimal parameter combination is found. The experimental results are combined with simulation predictions to verify and optimize the process parameters and achieve more precise non-equilibrium tissue regulation.
4. The method for controlling in-situ self-generated nano-precipitates during laser selective melting of high-strength and heat-resistant aluminum alloy according to claim 1, characterized in that: In step 3, the influence of the solution temperature, solution time, and quenching medium on the Al-Cu-X alloy obtained by additive manufacturing is studied; while eliminating the low-melting point non-equilibrium phase that may exist in the alloy, the solution process parameters that can completely dissolve the grain boundary θ-Al2Cu phase are obtained, and the fine-grained structure under the action of the magnetic field is retained in the solution structure as much as possible; According to the results of thermodynamic equilibrium analysis of different nano-precipitated phases, a multi-step regression re-aging heat treatment process is designed. The core of the process is to avoid different precipitated phases, so that two or more phases are precipitated alternately, and the nano-precipitated phase presents a multi-layer composite structure, thereby avoiding the occurrence of thermal coarsening of the nano-precipitated phase. The high-temperature performance of the Al-Cu-X alloy after multi-step solution-aging was tested, and its high-temperature tensile strength was analyzed. The microalloying design and precipitation phase screening criteria of the Al-Cu alloy were verified, and the in-situ self-generated nanophase precipitation strategy of the Al-Cu-X alloy was obtained, achieving a significant improvement in the heat resistance of aluminum alloy materials in the range of 300℃-400℃.
Citation Information
Cited By
Laser welding method for enhancing glass-metal by spraying nano-particles through ultrasonic waves
CN121289757A
Rare earth synergistic refining high-toughness aluminum-lithium alloy component optimization method for additive manufacturing
CN122164895A